Fathers' Lived Experiences of Miscarriage. (April 2018) - Wagner, Nathaniel J.; Vaughn, Colin T.; Tuazon, Victor E.
A phenomenological study was conducted to examine the lived experiences of fathers who have experienced miscarriage. Miscarriage is defined as pregnancy loss prior to 24 weeks of gestation. Eleven fathers participated and discussed their personal experiences before, during, and after the pregnancy and miscarriage. Six major themes emerged that depicted fathers shared experiences including (a) expectations of fatherhood, (b) conceptions of the pregnancy and personhood, (c) impact of the miscarriage setting, (d) immediate response to the event, (e) perceptions of support from others, and (f) overall experiences of disenfranchisement. Implications for family therapists working with families that have experienced miscarriage and future research recommendations are discussed.